2018
DOI: 10.1007/s11064-018-2592-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Induced Hyperhomocysteinemia with Alzheimer’s Disease-Like Neurodegeneration in Rat Cortical Neurons After Global Ischemia-Reperfusion Injury

Abstract: Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder that results in massive hippocampal and neocortical neuronal loss leading to dementia and eventual death. The exact cause of Alzheimer's disease is not fully explored, although a number of risk factors have been recognized, including high plasma concentration of homocysteine (Hcy). Hyperhomocysteinemia (hHcy) is considered a strong, independent risk factor for stroke and dementia. However, the molecular background underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 55 publications
4
43
0
1
Order By: Relevance
“…It suggests that the dose and duration of Met intake (2 g/kg within 28 days) is not linked with the clearly visible signs of neuronal disintegration in the CA1 hippocampal region. On the other hand, hHcy induced by subcutaneous administration of Hcy for 14 days was manifested by remarkable disintegration of neuronal tissues detected by FluoroJade staining in the cerebral cortex and hippocampus [10,11]. This indicates the diverse effect of hHcy induction, which is probably linked with the direct toxic impact of Hcy or its metabolites.…”
Section: Histo-morphological Changes In the Brain After Met Diet-indumentioning
confidence: 99%
See 1 more Smart Citation
“…It suggests that the dose and duration of Met intake (2 g/kg within 28 days) is not linked with the clearly visible signs of neuronal disintegration in the CA1 hippocampal region. On the other hand, hHcy induced by subcutaneous administration of Hcy for 14 days was manifested by remarkable disintegration of neuronal tissues detected by FluoroJade staining in the cerebral cortex and hippocampus [10,11]. This indicates the diverse effect of hHcy induction, which is probably linked with the direct toxic impact of Hcy or its metabolites.…”
Section: Histo-morphological Changes In the Brain After Met Diet-indumentioning
confidence: 99%
“…Our previous works documented that subcutaneous administration of Hcy in rats led to the development of mild hHcy [10][11][12]. This hHcy condition resulted in the disintegration of neuronal tissue in the cerebral cortex as well as the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Tau protein accumulated in the blood after a ischemia-reperfusion brain episode [78,79] can cross the ischemic blood-brain barrier and tau protein originating from serum can cause a stronger tau protein pathology in the brain parenchyma [80]. Ischemia-reperfusion brain injury with ischemic insufficiency of the blood-brain barrier [7,[81][82][83][84][85] initiates tau protein phosphorylation [53,54,56,57,77], and phosphorylated tau protein may cause damage to the blood-brain barrier, leading to harmful feedback reactions [74]. The permeability of the blood-brain barrier may exacerbate neuropathology through the tau protein from blood in brain damage as a result of ischemia-reperfusion by increasing its level in brain tissue, which suggests that the ischemic-reperfusion episode of the brain may play an important role in the growth of the blood tau protein level [78][79][80].…”
Section: Tau Protein In the Blood After Brain Ischemia And Ischemic Bmentioning
confidence: 99%
“…The formation of neurofibrillary tangles was observed after focal ischemia-reperfusion injury of the brain on the side of massive cerebral infarction in humans (Table 1) [54]. In addition, the combination of total brain ischemia with hyperhomocysteinemia in rats led to enormous neuronal changes in the hippocampus and cortex caused by hyperphosphorylated tau protein (Table 1) [56]. The above study reported a 695-fold increase in hyperphosphorylated tau protein-positive neurons in the ischemic brain compared to the control [56].…”
Section: Phosphorylation Of Tau Protein After Brain Ischemiamentioning
confidence: 99%
“…Choline supplementation in a mouse model of AD ameliorated cognitive functions in the first and second generations of mice and reduced the levels of homocysteine in their brain. Elevated levels of homocysteine have been linked to increased risk of AD development [102]. These observed changes in the AD mouse model in response to choline supplementation correlated with alteration in the expression of key genes related to inflammation, histone marks changes and neuronal death [100].…”
Section: Choline Other Methyl Donors and The Aging Brainmentioning
confidence: 99%